A systematic review of coach and parent knowledge of concussion. (January 2020) - Feiss, Robyn S; Lutz, Molly; Moody, Justin R; Pangelinan, Melissa M
Coach and parent knowledge of concussion is essential for the prevention, appropriate diagnosis, management, and return-to-play of youth athletes. This systematic review examined concussion knowledge of coaches and parents of youth athletes including general knowledge, sign and symptom recognition, management, and return-to-play protocols. Six databases were searched for studies that evaluated baseline knowledge levels of coaches and parents of youth athletes regarding concussion. A total of 17 articles (out of 1500 articles) met selection criteria. Coaches and parents could identify common signs and symptoms of concussion (e.g. headaches, dizziness, etc.) but were less aware of emotional symptoms (e.g. sadness or mood swings). Coaches were unaware that youth athletes may require more time to recover from a concussion compared to adults. Parents lacked knowledge regarding proper concussion management and return-to-play guidelines. Physicians were the main source of information for parents, while coaches and athletic trainers were the least utilized. There were clear gaps in both coach and parent knowledge of concussion. Future education programs should provide pediatric-specific information for concussion management, recovery, and return-to-play. Additional efforts are needed to increase communication and knowledge transfer between coaches, medical staff, and parents.